Pengaruh Akhir Pekan dan Pengaruh Januari di Bursa Efek Indonesia - Paul Augustin Tarigan; Adler Haymans Manurung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Based on the analysis of stock returns during this research period, which refers to year-by-year analysis outlined within the research timeframe, it can be observed that there is a variation in both negative and positive return rates. According to the processed data, it is known that in the year 2022, only Thursday returns had an impact on Monday returns. Thursday in 2022 had a positive influence on Monday returns in 2022. Additionally, based on the processed data, it is also found that in the year 2023, Wednesday and Friday returns could affect Monday returns. Statistically, it is concluded with 95% confidence that Monday trading volume does not affect Monday returns. Furthermore, it is statistically concluded with 95% confidence that January trading volume does not influence January returns. Based on the combined results of 2022 and 2023, it is evident that Stock Prices on Tuesday, Wednesday, and Thursday can influence Stock Prices on Monday. Statistically, it is concluded with 95% confidence that Stock Prices from February to December positively affect Stock Prices in January.